Performance comparison of the single-refrigerant cascade refrigerating system. (November 2022) - Sun, Zhili; Quan, Jianhua; Wang, Yi'an; Li, Ruishen; Peng, Jie; Zhang, Haoran; Xu, Jiapei; Sun, Huan; Tian, Shen; Dong, Shengming; Hu, Kaiyong; Chen, Wenxiang
Abstract: In the food refrigeration industry, the single-stage compression refrigerating system cannot meet the operating conditions of a high-pressure ratio when the evaporating temperature decreases. The cascade refrigerating system (CRS) is an alternative technical solution to solving the mentioned problem. This paper studied single-refrigerant pairs used in CRS. The single-refrigerant pairs R32/R32, R125/R125, R1270/R1270, R143a/R143a, R404A/R404A, R407A/R407A, R410A/R410A, and R507A/R507A were adopted to evaluate their operating characteristics compared with those of the traditional R23/R404A CRS. The operation adaptability of the compressor, the optimal operating parameters, the coefficient of performance (COP), and the seasonal energy efficiency ratio (SEER) were analyzed under different single-refrigerant pairs. The results show that the COP of the traditional CRS can be improved by using single-refrigerant pairs. The COP of R32/R32, R125/R125, R1270/R1270, R143a/R143a, R404A/R404A, R410A/R410A, and R507A/R507A were improved by 19.48%, 8.08%, 21.54%, 14.33%, 11.00%, 15.64%, and 12.11%, respectively. In addition, the SEER of the single-refrigerant CRS was higher than that of R23/R404A CRS. This could reduce energy consumption and save energy in typical cities in five major climatic zones of China. Considering COP, flammability, and safety, the application of R1270/R1270 and R32/R32 in a CRS with a low refrigerant charge is recommended. Meanwhile, R410A/R410A may be used in a CRS with a large refrigerant charge. These results provide a theoretical basis for the application of the single-refrigerant CRS.